2021
DOI: 10.1680/jgein.20.00038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aperture ratio on the cyclic shear behaviour of aggregate-geogrid interfaces

Abstract: In order to study the effect of aperture ratio (geogrid aperture size (AS)/average particle size (D50)) on the shear behaviour of aggregate–geogrid interfaces, a series of monotonic direct shear (MDS) tests, cyclic direct shear (CDS) tests and post-cyclic monotonic direct shear (PCDS) tests were carried out on two particle-shaped reinforced interfaces at five values of AS/D50. The cyclic shear behaviour of the two interfaces under three displacement amplitudes is discussed, and the interface shear characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…During this phase, the interfacial residual strength does not undergo significant alterations, and the geogrid-soil interface displays shear-softening characteristics. This result is very similar to the experimental results of Wang et al [25]. The possible cause of this phenomenon is that the value of σ is too high, which exacerbates the deformation and wear of the grid during the shearing process.…”
Section: Methodssupporting
confidence: 91%
“…During this phase, the interfacial residual strength does not undergo significant alterations, and the geogrid-soil interface displays shear-softening characteristics. This result is very similar to the experimental results of Wang et al [25]. The possible cause of this phenomenon is that the value of σ is too high, which exacerbates the deformation and wear of the grid during the shearing process.…”
Section: Methodssupporting
confidence: 91%
“…Laboratory direct shear test studies have shown that different stress levels and different types of fillers cause great differences and complexities in the shear strengths and deformations of the interface between the reinforcement and the soil [15][16][17]. In a study of RCA applied to reinforced structures, Wang et al [18] showed that adding a geogrid to RCA under repeated loading has a greater impact on the permanent deformation and elastic modulus. Touahaia et al [19] studied the shear strength characteristics of RCA materials and showed that the presence of geosynthetics led to a marked increase in the shear resistance of the material and greatly restricted the deformation of a sample.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the influence of grain on the shear zones of the interface was also studied by using the finite element software ABAQUS. Wang [25] studied the influence of the aperture ratio (geogrid aperture size/medium grain size) on the mechanical characteristics of the interface. Ghaaowd [26] performed a large-scale pullout trial to explore the interaction between the maximum particle size of tire-derived aggregate (TDA) and geosynthetics and observed combined tensile-pullout failure subjected to higher normal loading.…”
Section: Introductionmentioning
confidence: 99%